2010
DOI: 10.1111/j.1460-2695.2010.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of universal joint of a compliant platform

Abstract: A B S T R A C T The paper describes a methodology for computation of fatigue reliability of universal joint in an articulated offshore tower. Failure criteria were formulated using the conventional Palmgren-Miner rule (S-N curve approach) and the fracture mechanics (F-M) principle. The dynamic analysis of double hinged articulated tower under wind and waves is carried out in time domain. The response histories of hinge shear stresses are employed for the reliability analysis. Advanced first-order reliability m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It demands analysis of articulated towers under combined action of wind, wave, and current loads, Kunpeng et al (2016). The combined action may also cause fatigue damage to articulated joints as they are subjected to significant stress reversals as reported by Zaheer and Islam (2010). It shows the critical impact of the combined wind, wave, and current action on compliant platforms like articulated towers.…”
Section: Introductionmentioning
confidence: 76%
“…It demands analysis of articulated towers under combined action of wind, wave, and current loads, Kunpeng et al (2016). The combined action may also cause fatigue damage to articulated joints as they are subjected to significant stress reversals as reported by Zaheer and Islam (2010). It shows the critical impact of the combined wind, wave, and current action on compliant platforms like articulated towers.…”
Section: Introductionmentioning
confidence: 76%
“…Different crack locations correspond to different types of vector B in Eq. (16). Equation (18) can be applied to determine the corresponding torque variations.…”
Section: Methods For Crack Detectionmentioning
confidence: 99%
“…Nie et al 15 discussed and modelled the fatigue life of robots with flexible joints subjected to percussive impact forces. Zaheer and Islam 16 evaluated the fatigue reliability of a universal joint in an articulated offshore mechanism. The conventional Palmgren-Miner ruler and the fracture mechanics were applied to develop a fatigue model.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability methods applied to account for inherent uncertainties with respect to selecting an optimal tool for making a proper decision, which enables a balance between design criteria, and inspection and repair plans include S-N and FM formulations. In [41,42], a methodology for the calculation of fatigue reliability (FR) of universal joint in an articulated offshore tower was presented. It was reported that the S-N curve approach yields a significantly conservative approximation of POF [Type here] when compared to the FM approach.…”
Section: Ziegler and Muskulusmentioning
confidence: 99%